Chemical and microbiological changes in acid ensiled visceral waste of Indian major carp Catla catla (Hamilton) with emphasis on proteases - Bhaskar, N; Mahendrakar, N S (Indian Journal of Fisheries, 2011)
Processing of fish generates considerable quantities of highly perishable wastes including visceral mass. The present investigation was carried out to evaluate the effect of acid ensilaging on the chemical and microbiological characteristics of the visceral wastes of the Indian major carp, Catla catla, with the main objective of stabilizing the proteases. Acidification of visceral mass resulted in significant (P≤0.05) reduction in pH to 3.3 from the initial value of 6.2, however, it did not change the moisture, fat and ash content significantly (P≥0.05) during the storage period of 4 weeks at an ambient temperature of 27±2°C. Buffer extractable proteins (BEP), although decreased immediately after acidification (P≤0.05), showed an increase up to 2 weeks of storage and then decreased later during further storage. Fresh visceral waste of Catla catla has considerable protease activity especially neutral proteases. Specific activity (U mg-1 protein) of acidic, neutral and alkaline proteases showed marked decrease during storage (P≤0.05) from the initial values of 4.2, 13.2 and 4.7 respectively. Acid ensilaging negatively affected the proteases present in the fish visceral wastes with alkaline proteases being the most affected.